2021
DOI: 10.3390/nu13020296
|View full text |Cite
|
Sign up to set email alerts
|

Is There a FADS2-Modulated Link between Long-Chain Polyunsaturated Fatty Acids in Plasma Phospholipids and Polyphenol Intake in Adult Subjects Who Are Overweight?

Abstract: Dietary polyphenols promote cardiometabolic health and are linked with long-chain polyunsaturated fatty acids in plasma phospholipids (LC-PUFA). The FADS2 polymorphisms are associated with LC-PUFA metabolism and overweight/obesity. This 4-week study examined the link between polyphenol intake, FADS2 variants (rs174593, rs174616, rs174576) and obesity in 62 overweight adults (BMI ≥ 25), allocated to consume 100 mL daily of either: Aronia juice, a rich source of polyphenols, with 1177.11 mg polyphenols (expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In a large Italian population sample of obese children, a common variant in the gene FADS1 (rs1535) has been associated with BMI [48]. SNPs of FADS2 (rs174593, rs174616, and rs175576) have been documented to play a role in the interaction of polyphenols with PUFA levels and parameters of obesity [72], while lower levels of TC, LDL-C, and HDL-C have been associated with the minor allele of FADS1 rs174547 [73]. Regarding the incidence of DM2T, one study found a positive association between D6D activity and FADS1 rs174550, but, on the other hand, a clear inverse relation between the same SNP and D5D activity [43].…”
Section: Discussionmentioning
confidence: 99%
“…In a large Italian population sample of obese children, a common variant in the gene FADS1 (rs1535) has been associated with BMI [48]. SNPs of FADS2 (rs174593, rs174616, and rs175576) have been documented to play a role in the interaction of polyphenols with PUFA levels and parameters of obesity [72], while lower levels of TC, LDL-C, and HDL-C have been associated with the minor allele of FADS1 rs174547 [73]. Regarding the incidence of DM2T, one study found a positive association between D6D activity and FADS1 rs174550, but, on the other hand, a clear inverse relation between the same SNP and D5D activity [43].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a larger group of study participants at cardiovascular risk, from which our substudy group was sorted out, there had also been a significant AA/EPA reduction in aronia polyphenols consumers, noting that this reduction had been due to a significant decrease in AA, while EPA had not increased significantly (23). Furthermore, in a recent study that has investigated the link between FADS2 gene variants, fatty acid metabolism, and aronia polyphenol intake in the overweight, there was a trend of AA/EPA reduction in individuals who consumed aronia juice, compared to placebo consumers (45). There has been evidence for an association between total plasma AA and ischemic stroke (46), and the increase in circulating EPA levels has been shown to have beneficial effects on cardiovascular health (47).…”
Section: Discussionmentioning
confidence: 99%